To Study Morphological and Laboratory Changes in the Organs of the Oral Cavity and Periodontal Tissues in Adult Women - Juraeva Oygul Alisher Kizi; Hajimuradov Burkhan Ravshanovich (International Journal of Scientific Trends, 2024)
During menopause, irreversible changes in the hormonal function of the ovaries occur, the concentration of estrogens decreases. It is during this period that a progressive increase in various diseases is noted [8]. The study of the dental status in menopausal women has proven the existence of a relationship between a decrease in estrogen concentration and a sharp increase in dental diseases [4]. Because the oral mucosa and salivary glands contain estrogen receptors, changes in hormonal levels can be seen directly in the mouth. Leimola-Virtanen et al confirmed the presence of estrogen mRNA and immunoreactive protein in the oral mucosa and salivary glands, which also confirms its biological role [11]. Thus, the climacteric period is characterized by a disorder of metabolism and function in the tissues of the oral cavity [6]. As a result, tooth loss, periodontal disease, increased bone resorption of the alveolar processes are observed.